(untitled) (Nigerian Journal of Physiological Sciences, 2021)
The in vivo antimalarial and antidiabetic activity of extract of Camellia sinensis (ECS) in alloxan-induced diabetic and Plasmodium berghei-infected mice were investigated. Eighty-four BALB/c mice divided into sets 1 & 2 infected with P. berghei and 2 & 3 injected with alloxan received either distilled water, ECS (300mg/kg), Chloroquine (CQ-10mg/kg) or Metformin (250mg/kg). Results showed significant increases (p<0.05) in percentage parasitaemia of P. berghei-infected mice treated with ECS and P. berghei-diabetic mice. Furthermore, ECS significantly decreased (p<0.05) blood glucose and PCV in diabetic and P. berghei-diabetic mice. ECS regenerated pancreatic islet cells in P. berghei-infected-diabetes but lacked appreciable antimalarial activity